Growth modelling of Scots pine stands within Northern Prydniprovsk Steppe of Ukraine - Lakyda, P. I.; Lovynska, V. M. (Forestry and Forest Melioration, 2020)
Introduction Scots pine (Pinus sylvestris L.) is the main forest-forming species within Northern Prydniprovsk Steppe of Ukraine. Taking into account dynamic changes in the stands here, it is an urgent task to develop dynamic growth class scales and construct proper growth yield tables. The tables reflect not only the current state of the stands, but also predict their age-related changes. The fact that there are no such tables for the pine stands in the Northern Steppe of Ukraine determined the direction of this work. The aim of the study was to establish patterns in dynamics of biometric indicators of the modal pine stands and to develop yield tables for the pine stands of Dnipropetrovsk Region. Materials and Methods The research was carried out based on the stand-wise database of Ukrderzhlisproekt Production Association and experimental data of temporary sample plots within Dnipropetrovsk Region. To analyse growth dynamics, model trees were selected according to the category of their upper heights. Modelling of the upper and middle heights of the pine stands was performed using the Mitscherlich growth function. The biometric indicators of the model trees and stands were determined by means of generally accepted methods in forest mensuration. Results The results of the upper and middle stand heights modelling of Scots pine showed high rates of determination coefficients and significant regression coefficients. According to the modelling results, a dynamic rating scale was constructed. It characterizes features of the pine stands growth within Dnipropetrovsk Region. The base age is 60 years. The height growth of the modelled curves of seed pine stands comparing to the modified modern growth class scale, demonstrated a reduction of pine growth in the studied region. Deviations of the descending type, compared to the current growth class scale, are particularly well-showed for the stands of lower growth classes (IV, V), starting from the age of 70 years. Based on the worked out dynamic growth scale, we developed calculation models of other biometric indices, such as stand mean diameter, mean growing stock, form factors, basal area sum, number of trees per 1 ha, average and current increments for part of growing stands and their removed part (due to natural thinning or forest management activities). The fragment of yield tables of modal pine stands of I growth class is presented. The comparative evaluation of the results obtained for the growing stock of pine stands with a similar parameter for artificial pine stands in Ukrainian Polissia and in the Forest-Steppe and Northern Steppe regions of European part are given. Conclusions The obtained results will help to assess a current state of pine stands in Dnipropetrovsk Region as well as to predict the dynamics of their changes. The developed yield tables as a regulatory information support will allow evidence-based forest management taking into account regional peculiarities of pine growth. 3 Figs., 5 Tables, 12 Refs. Key words: Pinus sylvestris L., relative height, modelling, dynamic growth class scale, Mitscherlich function.